2001
DOI: 10.1081/iph-100107339
|View full text |Cite
|
Sign up to set email alerts
|

NEUROPEPTIDES MODULATE A MURINE MONOCYTE/MACROPHAGE CELL LINE CAPACITY FOR PHAGOCYTOSIS AND KILLING OFLEISHMANIA MAJORPARASITES

Abstract: Host-parasite interactions and their outcome constitute a critical and challenging step in disease establishment in cutaneous leishmaniasis. In the present in vitro study we investigated the possible modulating effects of both sensory and autonomic neuropeptides that normally exist in human and mouse skin, on the uptake and leishmanicidal capacity of macrophages on Leishmania (L.) major parasites, using a monocyte/macrophage murine cell line (Raw 264.7). The sensory neuropeptides somatostatin (SOM), calcitonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 43 publications
2
19
0
1
Order By: Relevance
“…There is a growing list of neuropeptides like MCH that modulate monocyte/macrophage functions (15,17). For instance, substance P can elicit a variety of responses in monocytes, including differentiation (18), phagocytosis (15), production of proinflammatory cytokines (19), and chemotaxis (20).…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing list of neuropeptides like MCH that modulate monocyte/macrophage functions (15,17). For instance, substance P can elicit a variety of responses in monocytes, including differentiation (18), phagocytosis (15), production of proinflammatory cytokines (19), and chemotaxis (20).…”
Section: Discussionmentioning
confidence: 99%
“…However, enhancement of chemotaxis by the SRIF analogue octreotide has been described as well (Ahmed et al, 2001;Ahmed et al, 1998;Wiedermann et al, 1993).…”
Section: Effects Of Srif On the Functions Of Monocytes And Macrophagesmentioning
confidence: 99%
“…In vitro, NPY was found to stimulate macrophage functions, including chemotaxis, in some studies but inhibited these responses in others (19,23,45,46). NPY was also found to inhibit the expression of costimulatory molecules on monocytes in a rat model of experimental autoimmune encephalitis (47).…”
Section: Discussionmentioning
confidence: 99%
“…NPY is also upregulated in the cerebrospinal fluid of patients with HIV encephalopathy, although the effect of this upregulation remains unknown (18). Recent studies with macrophage-like cell lines or isolated macrophages have demonstrated that NPY can influence macrophage activation (19)(20)(21)(22)(23)(24). Additionally, NPY has been found to inhibit interleukin 1␤ (IL-1␤)-induced activation of microglia (25,26), the primary resident myeloid cell type in the CNS.…”
mentioning
confidence: 99%